MENTAL HEALTH IN BUDDHIST MEDITATION: A GLOBAL SOUTH LENS OF INDONESIAN AND ENGLISH SOURCES - Prastowo, Fuji Riang; Yuniarti, Kwartarini Wahyu; Yulianti (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study investigates the representation of mental health issues associated with Buddhist meditation in academic literature, emphasizing English and Indonesian sources from a Global South viewpoint. The research employs a systematic literature review, utilizing subscription-based English databases like Scopus and open-access Indonesian platforms, including Google Scholar, accessed through Publish or Perish. This methodology selects 60 pivotal publications for their citation impact, timeliness, and historical importance. The investigation utilizes Visvanathan's Cognitive Justice framework within the Indonesian Consortium for Religious Studies to rigorously assess the epistemic inclusivity of knowledge systems.The results indicate three notable insights. Buddhist meditation is universally acknowledged across various sources as a fundamental practice associated with mental health discourse. Secondly, both English and Indonesian texts emphasize the interaction between Buddhism as an Eastern spiritual tradition and Western psychological and psychiatric paradigms. Indonesian sources specifically examine the impact of state hegemony on Buddhist meditation, highlighting its designation as a religion under Indonesia's monotheistic framework. The study highlights the socio-political factors influencing sacred and profane tales in Indonesia, especially with state-imposed religious classifications. This research highlights critical insights into the impact of socio-political processes in the Global South on the relationship between Buddhist meditation and mental health.